EDUCATION FUND MANAGEMENT STRATEGIES IN ENSURING PRIMARY SCHOOL QUALITY - Rahmattullah, Rahmattullah; Sariakin, Sariakin; Kasmini, Lili (Universitas Labuhanbatu, 2025)
Purpose – This study aims to analyze the strategy of managing educational funds implemented at SDN 61 Banda Aceh to support the assurance of educational quality. Using a SWOT analysis approach, this research evaluates the strengths, weaknesses, opportunities, and threats in the school’s financial management.Methodology – The research employs a qualitative approach with data collection techniques including interviews, observation, and analysis of the school’s financial documents.Findings – The study shows that SDN 61 Banda Aceh possesses several strengths in fund management, such as transparency in budget utilization and the involvement of the school committee. However, there are weaknesses related to delayed disbursement of funds from the government and a lack of capacity among administrative staff in performance-based financial management. Opportunities include enhancing the capacity of school financial managers through training and leveraging technology for financial recording and reporting. Meanwhile, the main threats faced are the uncertainty of budget policies and the potential for fund misuse due to weak external oversight systems. Significance – The implementation of more structured strategies, such as strengthening School-Based Management and increasing transparency through stricter financial audits, is recommended. This approach is expected to support continuous improvements in educational quality at SDN 61 Banda Aceh.